Catalyst Losses and Air Flow Rate Effect on Cyclone Efficiency at Residue Fluidized Catalytic Cracking Unit - Rizka Wulandari Putri; Umi Sarah; Ali Hanif; Rahmatullah; Selpiana; Muhammad Haviz (CHEESA: Chemical Engineering Research Articles, 2025)
Residue Fluidized Catalytic Cracking Unit (RFCCU) in the oil and gas industry is equipped with a regenerator that uses a cyclone to separate solid catalyst from reaction gases. Oxidation gases rise to the top of the regenerator before entering the cyclone stage. The cyclone inlet velocity depends on factors such as Main Air Blower (MAB) flow, dilute phase temperature, and dense bed temperature. Therefore, this study aimed to determine the effect of catalyst losses and combustion air flow rate on cyclone efficiency of RFCCU. The efficiency was determined simply by calculating catalyst losses compared to the catalyst inlet. The results showed that the dilute phase and dense bed temperature parameters had an indirect influence on cyclone inlet velocity. Furthermore, the separation efficiency of the device was 88% with 12 % catalyst loss by limiting the combustion air flow rate to a maximum value of 1,559 t/d. These limits should be met to prevent cavitation and reduce cyclone efficiency.